Towards a radical life. Social and political threads of Helen Keller’s activities - PAWLIK, SABINA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Sabina Pawlik, Towards a radical life. Social and political threads of Helen Keller's activities. Interdisciplinary Contexts of Special Pedagogy, no. 27, Poznań 2019. Pp. 151–161. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.27.07 Biographies of people with disabilities emphasising on their humanity and the value of this very special human experience may lead to questioning common assumptions about disability and people suffering from it. One of the best known historical figures among the people with disabilities was Hellen Keller, a deaf-blind American writer, educator and social activist. The article contains an attempt to challenge the myth of Keller as a “miracle child” by presenting her rich life and the most prominent aspects of her social and political activity.